2000
DOI: 10.1159/000028341
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic Evidence of Delta-Opioid Receptor Downregulation after Prenatal Stress in Offspring Rat Brain

Abstract: In order to visualize neuroanatomical alterations in specific brain regions, light microscopy autoradiography was carried out on offsprings (postnatal day 10) from female rats stressed in different periods of gestation and controls. Group 1 was subjected to restraint stress from day 2 to 6; group 2, from day 7 to 11; group 3, from day 12 to 16; group 4 from day 2 to 16. Group 2 showed decreases in δ-opioid receptor density in different hypothalamic regions. The decrease in δ-opioid receptor density was less ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…It is not clear why a parallel decrease in opioid receptor expression was also noted. However, previous studies have similarly reported a long-term increase in endogenous opioid peptide along with a concomitant decrease in mu and delta opioid receptor density in the lateral hypothalamus of offspring following gestational stress (Sanchez et al, 1996, 2000). Alternatively, opioid receptors are rapidly internalized following ligand binding, which would also result in a concomitant decrease in opioid receptor availability.…”
Section: Discussionmentioning
confidence: 91%
“…It is not clear why a parallel decrease in opioid receptor expression was also noted. However, previous studies have similarly reported a long-term increase in endogenous opioid peptide along with a concomitant decrease in mu and delta opioid receptor density in the lateral hypothalamus of offspring following gestational stress (Sanchez et al, 1996, 2000). Alternatively, opioid receptors are rapidly internalized following ligand binding, which would also result in a concomitant decrease in opioid receptor availability.…”
Section: Discussionmentioning
confidence: 91%
“…Glucocorticoid receptor density in the ventromedial prefrontal cortex (vmPFC) and limbic system, specifically the amygdala and hippocampus, has been proposed as a possible mechanism for environmental stress-cortisol-brain interactions relevant to psychopathology, as evinced in rodent research1112. Human work has further highlighted potential sensitivity in the amygdala-vmPFC pathway for emotional reactivity and recovery131415.…”
Section: Stress and Cortisolmentioning
confidence: 99%
“…These include a decrease in foetal bendorphin, CRH (Ohkawa et al, 1988) and noradrenaline production (Ohkawa et al, 1991). In the adult offspring, there is a reduction in pro-opiomelanocortin mRNA expression in the hypothalamus (Weinstock et al, 1992), and a down-regulation of brain opioid receptors (Insel et al, 1990;Sanchez et al, 1996;. The PS rats also show a significant alteration in their analgesic response to morphine (Kinsley et al, 1988) and a decrease in the opioid component of their exploratory behaviour in a novel situation (Poltyrev and Weinstock, 1997).…”
Section: Effect Of Maternal Administration Of Naltrexone On Behaviourmentioning
confidence: 99%
“…These include an alteration in cerebral asymmetry Alonso et al, 1991b) that is consistent with the loss of left-sided cerebral dominance, and is observed in humans with abnormalities in development and with schizophrenia (Yeo et al, 1997;Satz and Green, 1999), heightened anxiety, as seen in the poorer coping skills in the presence of unknown or alarming circumstances (Meijer, 1985;Fride et al, 1985;1986) and behavioural and physiological symptoms of depression (Secoli and Teixeira, 1998;Koehl et al, 1999;Rao et al, 1999;Brown et al, 2000). Prenatal stress may also increase the propensity for alcohol and drug addiction (Huttunen and Niskanen 1978;Deminiere et al, 1992), through permanent alterations in limbic opioid, benzodiazepine (BDZ) and dopamine receptors (Fride et al, 1985;Insel et al, 1990;Alonso et al, 1994;Henry et al, 1995;Sanchez et al, 1996;. This, and the other behaviour anomalies induced by prenatal stress are associated with increased activity and impaired feedback regulation of the hypothalamic pituitary adrenal (HPA) axis (Weinstock et al, 1992;Henry et al, 1994).…”
Section: Introductionmentioning
confidence: 99%